Gendered plants and plant categorization by gender: Classificatory and “storied” knowledge in trás-os-montes, portugal - Frazão-Moreira, Amélia (2018)
Background: An anthropomorphizing process arises out of classification systems, whereby analogy is drawn between the social differences of gender and the morphological and biological characteristics used to designate or classify plants. On the other side, it is observed that men and women categorize plants differently on the basis of their practices and knowledge. This paper addresses two assumptions: the consistent cognitive mechanisms of attributing gender to plants in classifications and the local differentiation of knowledge and social variability of categorization of plants based on gender. Methods: The data presented results from research carried out in Portugal in two rural villages, using participant observation, structured ethnobotanical interviews and free pile sorting task (79 interlocutors; among them 11 local experts). A literature review provided some examples from studies conducted in other contexts, which have been used to analyze and discuss our findings. Results: Gender differentiations are present in plants naming and identification. Plants morphologically similar can take different designations or have the same name with gender variations depending on people’s perceptions of female or male features. The survey conducted in these Portuguese case studies shows also a gender variability of knowledge, although knowledge about plants is usually quite shared. Conclusions: The mechanism of plant differentiation using gender attributes seems to be transcultural. However, the plant classification by gender must be explained from a local standpoint and knowledge about plants should be understood as a “storied knowledge”.